Improving Active Learning Performance through the Use of Data Augmentation - Fonseca, João (2023)
Fonseca, J., & Bação, F. (2023). Improving Active Learning Performance through the Use of Data Augmentation. International Journal of Intelligent Systems, 2023, 1-17. https://doi.org/10.1155/2023/7941878 --- Funding: This research was supported by three research grants of the Portuguese Foundation for Science and Technology (“Fundação para a Ciencia e a Tecnologia”): SFRH/BD/151473/2021 - MIT Portugal PhD Grant; DSAIPA/DS/0116/2019, and PCIF/SSI/0102/2017.